An Industry-wise Comparative Study of Industry 4.0 Status of Indian Firms - Ramanathaiah, Ramakrishnan Magge; Elluranand; Rani, Yavana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose - Industry 4.0 is reality. Indian firms must be at different stages of embracing Industry 4.0. This research paper tries to explore the status of Indian firms with regards to moving towards Industry 4.0. This paper also tries to capture the challenges companies are facing to call themselves Industry 4.0 ready. Approach –A virtual survey of Indian companies is carried out. Methodology is to survey companies by visiting their websites and other newspaper articles to collect data on various aspects of Industry 4.0 activities of top companies in two sectors. Findings – The research result shows that the two industries studied were much ahead in adopting Industry 4.0 relevant technologies. But there were other industries which were not even near totechnologies to be Industry 4.0 ready. Research Implications – The findings reveal there is huge scope in spreading awareness and thereby action required in several industries. Utility of the paper – Research paper definitely provides a basic understanding of status of companies in two industries with regards to Industry 4.0 readiness.